Crafting a comprehensive interview guide for Malaysian parents in sexuality education: methodological insights and best practices - Abdul Hamid, Siti Hazariah; Ellin, Mohammed Rasheedan; Mohd Arifin, Siti Roshaidai; Hasan, Haliza; Othman, Sajaratulnisah; Mohd Zain, Norhasmah (Universiti Putra Malaysia, 2025)
Introduction: Establishing a robust interview protocol is crucial for acquiring high-quality interview data, yet crafting such a protocol poses challenges, particularly for novice researchers and in sensitive areas like sexuality education. In the exploration of sexuality and reproductive health education, researchers encountered difficulties in posing questions to parents with diverse ethnic and sociodemographic backgrounds. Methods: This article illustrates the application of the 4-step Interview Protocol Refinement (IPR) Framework to the interview questionnaire, involving steps such as (1) aligning questions with research objectives(2) constructing inquiry-based conversations, (3) seeking feedback on protocols, and (4) pilot testing questionsIn this research, the participants were Malaysian parents with adolescents. Results: The IPR framework proves effective in enhancing the reliability and validity of the interview protocol. Two expert panels rectified deficiencies in the initial questionnaires through refinement processesand four parents involve in the validation phasethrough pilot testing Conclusion: The IPR framework greatly enhanced the reliability and validity of the interview protocol by iteratively refining questions. Further improvements in research quality can be achieved by implementing additional strategies during the stages of research tool validation and data analysis.